The Social Lives of Veiled Women: Exploring Religious Identity and Modern Society's Reactions - Suhendi, Hendi; Wahyudi, Ira (International Journal of Nusantara Islam, 2023)
The primary objective of this study is to investigate and gain a comprehensive understanding of the social experiences of women who wear the veil in their everyday lives. The study seeks to achieve two key objectives: first, to discern the motivations driving women to wear the veil, and second, to examine the social dynamics governing their utilization of the veil in daily life. Employing a qualitative method with a phenomenological approach, data collection was carried out through interviews and observations. The findings of this study shed light on the diverse motivations that drive veiled career women to wear the veil. These motivations are rooted in various causal factors, including experiences of disturbance, societal influences, concerns, and familial issues. The overarching objective for these women is to fortify their faith and safeguard themselves against undesirable behaviors. Moreover, the study reveals that the veil holds multiple meanings for career women who wear it, such as serving as reminders, protective elements, expressions of gratitude, symbols of communication, obligations, and even challenges. The dynamics of communication among women who wear the veil, as explored in this study, encompass interactions with their immediate environment, their social circles, and communication within the workplace. These interactions elicit a spectrum of responses and reactions, ranging from rejection and alienation to serving as role models and sources of inspiration for others considering the practice of wearing the veil. This research provides valuable insights into the complex interplay of motives, meanings, and social interactions surrounding the practice of veiling among career women